Anatomical and Functional Outcomes of Management Pediatric Retinal Detachment with High Myopia and History of Retinopathy of Prematurity: A Case Report: Poster Presentation - Case Report - Resident - Sadikin, Irma Suwandi; Yudantha, Anggun Rama (Majalah Oftalmologi Indonesia, 2023)
Introduction : To report the anatomical and functional outcomes of management of pediatric retinal detachment in children with high myopia and a history of retinopathy of prematurity. Case Illustration : A 9-year-old boy had a sudden visual loss two months ago. The complaint is accompanied by photopsia and floaters. No history of trauma or infection. He had a history of myopia (S-6.00) and ROP in both eyes. The VA of the right eye was no light perception, and the left eye was 1/60. A retinal detachment with the macula off was discovered in the posterior examination. The axial length was 21 mm. He underwent a scleral buckle with vitrectomy and internal limiting membrane (ILM) peeling for his left eye. After surgery, the visual acuity was 3/60 with the retina attached. Re- detachment was found three weeks after surgery. The patient was scheduled for a second phacoemulsification and vitrectomy surgery. One month later, the best visual acuity reaches 6/48 with S -8.00 D on his left eye. The complication of high intraocular pressure (IOP) after surgery was managed successfully. Discussion : Conclusion : Management of retinal detachment cases in children is challenging. Hence, a thorough understanding is crucial in order to achieve anatomical and functional success. Myopia in ROP eyes was mainly lenticular, with an alteration in the anterior chamber that contributed to the patient's refractive status change. We encourage preterm patients to have regular follow-up not only for refractive status but also for structural changes in the anterior segment until adolescence.